Salvaging of Hopeless Tooth by an Interdisciplinary Approach - Chopra, Priyanka; Gupta, Anjali; Tiwari, Ram (Journal of Orofacial Research, 2015)
Hemisection means removal of one root with accompaning crown portion of decayed mandibular molar. Hemisection saves the tooth instead of extraction. This article is about 15 years old boy with deep furcation involvement of mandibular molar treated by hemisection procedure.